Efficient Targeted Mutagenesis in Apple and First Time Edition of Pear Using the CRISPR-Cas9 System - Charrier, Aurélie; Vergne, Emilie; Dousset, Nicolas; Richer, Andréa; Petiteau, Aurélien; Chevreau, Elisabeth (Frontiers in Plant Science, 2019)
Targeted genome engineering has emerged as an alternative to classical plant breeding and transgenic methods to improve crop plants. Among other methods (zinc finger nucleases or TAL effector nucleases) the CRISPR/Cas system proved to be the most effective, convenient and least expensive method. In this study, we optimized the conditions of application of this system on apple and explored its feasibility on pear. As a proof of concept, we chose to knock-out the Phytoene Desaturase (PDS) and Terminal Flower 1 (TFL1) genes. To improve the edition efficiency, two different single guide RNAs (gRNAs) were associated to the Cas9 nuclease for each target gene. These gRNAs were placed under the control of the U3 and U6 apple promoters. Characteristic albino phenotype was obtained for 85 % of the apple transgenic lines targeted in MdPDS gene. Early flowering was observed in 93 % of the apple transgenic lines targeted in MdTFL1.1 gene and 9 % of the pear transgenic lines targeted in PcTFL1.1. Sequencing of the target zones in apple and pear CRIPSR-PDS and CRISPR-TFL1.1 transgenic lines showed that the two gRNAs induced mutations but at variable frequencies. In most cases, Cas9 nuclease cut the DNA in the twenty targeted base pairs near the protospacer adjacent motif and insertions were more frequent than deletions or substitutions. The most frequent edition profile of PDS as well as TFL1.1 genes was chimeric biallelic. Analysis of a sample of potential off-target sequences of the CRISPR-TFL1.1 construct indicated the absence of edition in cases of three mismatches. In addition, transient transformation with the CRISPR-PDS construct produced two T-DNA free edited apple lines. Our overall results indicate that, despite the frequent occurrence of chimerism, the CRISPR/Cas 9 system is a powerful and precise method to induce targeted mutagenesis in the first generation of apple and pear transgenic lines.